Tratamento de efluente de indústria de laticínios por duas configurações de biorreator com membranas e nanofiltração visando o reuso - Laura Hamdan de Andrade (2011)
Rising costs of water withdrawal and treatment and effluent discharge, added to enforcement of environmental laws, which are becoming more restrictive, are pushing industries to settle systems for water reuse. Although dairies industries represent an important economic activity, they are responsible for the generation of wastewater with high pollution potential. Conventional systems used for the treatment of these effluents may exhibit several problems that directly affect their efficiency, such as poor sludge settling properties and sensitivity to shock loads. Given these limitations, the membrane bioreactor (MBR) is presented as a promising process, because of its advantage of total removal of suspended solids and production of effluents with high quality. Moreover, its combination with nanofiltration (NF) may consist of an efficient system for generating water for reuse. Thus, the aim of this study was to propose a new route for treatment and reuse of wastewater from a dairy industry which consists of an association of MBR and NF. The research was divided into four steps: first, raw and post-flotation effluent of a dairy industry were characterized and the one that would be fed into the MBR was selected; then the best conditions of hydraulic retention time and solids retention time of the MBR were determined in terms of best pollutant removal efficiency and fouling; on the third step, the performance of a new configuration of MBR, which was developed aiming to provide less fouling, was compared with that of conventional bioreactor with membrane submerged at biological tank; and finally the better operational conditions for the nanofiltration of the permeate of the MBR were determined and the feasibility of reuse of treated effluent was verified. The effluent selected as feed of the MBR was the post-flotation, given its greater biodegradability. The MBR was operated with hydraulic retention times (HRT) of 7.6 and 5.6 hours and solids retention times (SRT) of 80, 60 and 25 days, and removal efficiencies of organic matter and color above 98% were obtained for all conditions. The optimum operational conditions selected were HRT of 5.6 hours and SRT of 60 days. The shear caused by the sludge recirculation pump of the new configuration of the BRM had a great effect on biomass growth and release of metabolic substances. The NF permeate quality is enough for reuse as boiler, cooling and cleaning water and the concentrate’s characteristics allow its released in water bodies according to the parameters of legislation. Therefore, the combination of BRM and NF proved to be an excellent alternative for the treatment of effluent from the dairy industry enabling reuse.